Pendampingan Implementasi Kurikulum Merdeka Bagi Guru SMP MGMP Bahasa Indonesia Kota Tasikmalaya - Iis Lisnawati; Titin Setiartin R; Welly Nores K.; Laely Armiyati; Andini Primadani Putri; Elsi; Resti Andriyansyah; Khoerul Fikri Habibi (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2023)
Kurikulum Merdeka will be implemented at the secondary education level in 2024, even at the junior high school level, specifically for class VII, in the 2023/2024 academic year the Kurikulum Merdeka has been implemented. Implementation of the Kurikulum Merdeka requires teachers' understanding and readiness of the Kurikulum Merdeka with its various aspects and its applications. Realistic conditions in the field show that junior high school teachers do not fully understand the Kurikulum Merdeka, especially about Learning Outcomes, Learning Objectives, Flow of Learning Objectives, and Teaching Modules and their modifications. The purpose of service activities is to increase knowledge, understanding, and produce learning tools related to these matters. Activities carried out in the form of workshops. The results of the activity show that the teachers have understood the concept of the Kurikulum Merdeka and its applications. This can be seen from the results of the work of the teachers in embodying this concept in the form of Learning Objectives Flow and Teaching Modules as lesson plans to be implemented. Thus, junior high school teachers at the Indonesian Language MGMP Tasikmalaya City are ready to implement the Kurikulum Merdeka.